2017
DOI: 10.1099/jgv.0.000777
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analysis of whole-genome sequences confirms inter-farm transmission of Aleutian mink disease virus

Abstract: Aleutian mink disease virus (AMDV) is a frequently encountered pathogen associated with mink farming. Previous phylogenetic analyses of AMDV have been based on shorter and more conserved parts of the genome, e.g. the partial NS1 gene. Such fragments are suitable for detection but are less useful for elucidating transmission pathways while sequencing entire viral genomes provides additional informative sites and often results in better-resolved phylogenies. We explore how whole-genome sequencing can benefit inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, the complete genomic sequence of the previously described CDV Asia-4 was not available. Even the relatively variable region is essential for exploring more distant relationship among the strains, due to a small number of informative sites, evolutionary analysis of partial genes have resulted in low resolution of phylogenetic trees and is limited for exploring the outbreak 27 . Thus, these partial sequences could not be gathered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complete genomic sequence of the previously described CDV Asia-4 was not available. Even the relatively variable region is essential for exploring more distant relationship among the strains, due to a small number of informative sites, evolutionary analysis of partial genes have resulted in low resolution of phylogenetic trees and is limited for exploring the outbreak 27 . Thus, these partial sequences could not be gathered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the issue of limited resolution of the phylogeny, a drawback with different partial sequences is that they sometimes result in different and conflicting tree topologies [ 17 , 19 ]. It has however been shown that by sequencing the entire AMDV genome the phylogenetic resolution is increased to a level where transmission routes between farms can be elucidated [ 24 , 25 ], however the costs associated with the next generation sequencing (NGS) approach are substantial.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). This has been mentioned previously [ 11 15 22 ], indicating that an analysis of the longer fragments or even the whole genome can build better, higher-resolution phylogenetic relationships.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the trade of breeding stock/equipment and the circulation of people between farms (workers, visitors, technical staff) can be involved in spreading the virus [ 21 ]. Accordingly, the application of molecular epidemiology has proved useful for tracking possible sources of AMDV infections [ 11 22 ]. This has encouraged many producing countries to characterize their AMDV strains molecularly, and study their relationship with strains from different regions and countries [ 14 15 23 24 ].…”
Section: Introductionmentioning
confidence: 99%